(Im)possible deletions in the Spanish DP - Saab, Andrés Leandro (IBERIA: An International Journal of Theoretical Linguistics, 2011)
This paper centers on the problem of identity in Spanish nominal ellipsis. It is argued that a purely formal identity condition on nominal ellipsis, as proposed in Depiante & Masullo (2001), is not a sufficient condition and a structural condition is added to the theory. Concretely, it is argued that nominal ellipsis only affects the nP layer (see also Ticio 2003 and Saab 2004a-b) excluding NumP as a possible target for non-pronunciation. This hypothesis not only accounts for the well-known fact that number, but not gender, can obviate the identity condition on ellipsis, but can also explains why some nouns in the left periphery of the DP cannot be elided even when an identical antecedent is available in the linguistic context. It is also shown that data from ellipsis reveal a non-uniform behavior of some morphosyntactic properties of Spanish nouns, in particular, with respect to gender resolution. It is proposed then that gender is a property on n that is resolved post-syntactically through certain information available on n itself or on Roots (such as the presence of a sex feature). This goes against a long lexicalist tradition in Spanish grammar including Depiante & Masullo (2001) and is in consonance with recent findings in Nunes & Zocca (2009) and Bobaljik & Zocca (2010). Finally, ellipsis data provide an interesting argument in favor of a late insertion approach for Roots and lead me to formulate an identity condition that dissociates functional morphemes and Roots.